An IoT-Based Model for Monitoring Soil pH, Temperature, and Moisture to Support Precision Agriculture - M. Abdul Qodir Jaelani; Muhammad Adie Syaputra; Budi Sutomo (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2026)
Manual measurement of soil pH, temperature, and moisture often produces fragmented field data that are difficult to use for periodic land monitoring. This study developed an Internet of Things-based prototype for monitoring soil conditions to support precision agriculture. The system integrated a soil pH sensor, a waterproof DS18B20 soil temperature sensor, a soil moisture sensor, an ESP32 NodeMCU, Wi-Fi communication, data storage, and a web-based dashboard. The research followed a prototype development model covering requirement analysis, system design, hardware and software implementation, testing, evaluation, and refinement. Field testing was conducted from February to April 2026 at 08:00, 12:00, and 16:00. The results showed that soil pH ranged from 6.47 to 6.70 with an average of 6.58, soil temperature ranged from 21.30°C to 28.61°C with an average of 24.57°C, and soil moisture ranged from 73.67% to 90.00% with an average of 87.71%. Functional testing indicated that the prototype could read, transmit, store, and visualize soil data through the dashboard during operation. The proposed model is feasible as an early-stage monitoring system for data-driven soil management, although future accuracy validation with calibrated instruments is still required.